Efforts to Preserve Bandrong Pencak Silat Arts at Padepokan Sampurnaning Jaya Bojonegara Banten - Triena Permatasari; Dwi Julianti Lestari; divia Agustiani muttain (Universitas Pendidikan Indonesia, 2022)
Pencak silat Bandrong is one of the cultural characteristics of the people of Banten who were born and developed around Serang and Cilegon. Many Bandrong silat hermitages still exist today, including the Sampuraning Jaya Padepokan. The purpose of this study is to describe the efforts of Padepokan Sampuraning Jaya in preserving Bandrong Banten Pencak Silat which includes history, development and factors that support the preservation of Bandrong pencak silat art. Various works of art that have produced achievements have been obtained by this hermitage, and have published or promoted them in the form of multimedia, so that Pencak Silat Bandrong Banten can preserve the culture or characteristics of the Banten people, and become the pride of the next generation.